W-mass prediction in the complex NMSSM - Dao, Thi Nhung; Gabelmann, Martin; Muehlleitner, Margarete (Communications in Physics, 2025)
In this work, we present our recent calculation of the $W$ boson mass in the complex NMSSM, which includes all state-of-the-art higher-order supersymmetric corrections to $Δ r$. In particular, we include the full one-loop corrections and the leading and sub-leading two-loop corrections $\mathcal{O}(α + α_tα_s + \left(α_t+α_λ+α_κ\right)^2)$ from the $ρ$ parameter. We show some numerical investigations of the dependence of $Δρ$ on the renormalization schemes and of the dependence of $M_W$ on some selected parameters. We also discuss comparisons between some public tools which compute $M_W$ in the NMSSM. Finally we present a new version of the public Fortran code, {\tt NMSSMCALC}, including a new $M_W$ prediction.